Evaluation of Epistemic Beliefs Self-Report Questionnaires in the Czech Middle School History Classroom - Jaroslav Říčan; Ondřej Pešout (Pedagogika, 2023)
Epistemic beliefs are gaining increasing importance in social science education in Czechia. Recent literature has demonstrated findings linking epistemic beliefs with various academic skills, including achievement and reading comprehension. The present study aims to explore the epistemic beliefs of adolescents specific to the domain of history. The study reviews research literature on ontological changes in students’ epistemic beliefs and their reasoning within the domain of history since the 1950s, with a particular focus on various models and measurement. The empirical part of the study investigates adapted self-report questionnaires on the epistemic beliefs of adolescents in Czech history classes in the upper grades of middle school. In the first step, the selected questionnaires were back-translated and refined by iterative sets of cognitive interviews. The finalised sets of items were administered in seventh-, eighth-, and ninth-grade classes (N = 303) in May and June 2021. The confirmatory factor analysis and follow-up correlational analysis demonstrated various degrees of support for the dimensions of the Epistemic and Ontological Cognition Questionnaire, for the dimension of Value of Integration Information, and for the dimension of Historical Methodology in Generating Historical Knowledge. Reading comprehension correlated positively with epistemic belief dimensions related to epistemic criteria of justification by multiple sources, the value of integration information, and historical methodology. Academic achievement in the form of the end-of-grade marks obtained in the subjects of history and Czech language did not show a consistent relationship with the epistemic beliefs. The potential practical and research uses of the self-report questionnaires that were investigated in regular classroom instructions are discussed.